2003
DOI: 10.1590/s1677-04202003000100003
|View full text |Cite
|
Sign up to set email alerts
|

Leaf anatomy and carbon isotope composition in Coffea species related to photosynthetic pathway

Abstract: Possible presence of vascular bundle sheath cells and its relation to photosynthetic pathway, leaf anatomy and carbon isotope composition (delta13C) were examined in six species of genus Coffea: C. arabica (cvs. Catuaí Vermelho, Mundo Novo, Bourbon Vermelho and Icatu Amarelo), C. canephora (cvs. Apoatã and Guarini), C. liberica, C. dewevrei, C. salvatrix and C. stenophylla. In all genotypes, the vascular bundle was surrounded by a layer of cells with numerous chloroplasts in a centrifugal position. Visually no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
(27 reference statements)
0
3
0
1
Order By: Relevance
“…A study of Rodríguez-López et al 45 with genotypes widely cultivated in state of Espírito Santo (clones 03 and 120) showed that saturating irradiance for leaf photosynthesis of conilon coffee at full sun is between 522–612 µmol photons m −2 s −1 . But, under Brazilian conditions, where coffee is commonly cultivated without shading, the plants must endure irradiance as high as 2000 µmol m −2 s −1 around midday 45 , 46 . This means that irradiance available for conilon coffee in these locations is around 3.5 times the irradiance saturation point, a fact that further contributes to exacerbate the negative effects of drought and heat.…”
Section: Resultsmentioning
confidence: 99%
“…A study of Rodríguez-López et al 45 with genotypes widely cultivated in state of Espírito Santo (clones 03 and 120) showed that saturating irradiance for leaf photosynthesis of conilon coffee at full sun is between 522–612 µmol photons m −2 s −1 . But, under Brazilian conditions, where coffee is commonly cultivated without shading, the plants must endure irradiance as high as 2000 µmol m −2 s −1 around midday 45 , 46 . This means that irradiance available for conilon coffee in these locations is around 3.5 times the irradiance saturation point, a fact that further contributes to exacerbate the negative effects of drought and heat.…”
Section: Resultsmentioning
confidence: 99%
“…Rada et al (1987) conducted this on Espeletia schultzii a composite species from South America and a found a decline in mesophyll, epidermis and cell size with increase in altitude. These findings are echoed by Carelli et al (2003) who found the lowest values of leaf δ 13 C in C . dewevrei , a C3 plant, with a decline in mesophyll cells.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, more than four out of five samples can be correctly classified. The difference of the Corinthian currants species tested might also contribute to their variation in terms of of δ 13 C, as it has been proven that different coffee species varied in δ 13 C [ 38 ]. In a similar study, Li et al [ 39 ] showed that carbon isotope ratio could be used to identify the geographical origins of Schisandra fruits in China.…”
Section: Resultsmentioning
confidence: 99%